2018
DOI: 10.1074/jbc.ra117.001145
|View full text |Cite
|
Sign up to set email alerts
|

The cytochrome P450 24A1 interaction with adrenodoxin relies on multiple recognition sites that vary among species

Abstract: Mitochondrial cytochromes P450 (P450s) are responsible for important metabolic reactions, including steps involved in steroid and vitamin D metabolism. The mitochondrial P450 24A1 (CYP24A1) is responsible for deactivation of the bioactive form of vitamin D, 1,25(OH) 2 D3. Its function relies on formation of a P450-redox partner complex with the ferredoxin and electron donor adrenodoxin (Adx). However, very little is known about how the Adx-CYP24A1 complex forms. In this study, we report the results of solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Except for the –OCH 2 – group, the substrate proton-heme iron distances for CYP1A2 WT, L382V, N312L, and L382V/N312L were very similar, ranging from 6.1 to 8.2 Å. These values are similar to the distances between hydroxylation sites and the heme iron reported for other P450 enzymes [ 15 , 17 , 22 , 23 , 24 , 25 , 26 ]. The distance between the protons of the –OCH 2 – group and heme iron in CYP1A2 N312L was about 7.84 Å, which is much longer than that in CYP1A2 WT (6.55 Å).…”
Section: Discussionsupporting
confidence: 76%
“…Except for the –OCH 2 – group, the substrate proton-heme iron distances for CYP1A2 WT, L382V, N312L, and L382V/N312L were very similar, ranging from 6.1 to 8.2 Å. These values are similar to the distances between hydroxylation sites and the heme iron reported for other P450 enzymes [ 15 , 17 , 22 , 23 , 24 , 25 , 26 ]. The distance between the protons of the –OCH 2 – group and heme iron in CYP1A2 N312L was about 7.84 Å, which is much longer than that in CYP1A2 WT (6.55 Å).…”
Section: Discussionsupporting
confidence: 76%
“…Expression and purification of WT and mutant CYP121A1 is described further under Supplementary data . Expression and purification of bovine adrenodoxin reductase and bovine adrenodoxin used in the activity assays were carried out as described previously 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Affinity constants were calculated by fitting the ligand concentrations plotted against the difference spectra showing either a red-shifted, type-I response (cYY) or a blue-shifted, type-II response (ketoconazole and imidazole). Data fitting was carried out using Prism GraphPad v7.05 using a single binding mode equation for hyperbolic binding as described previously 33 . Carbon monoxide (CO) binding spectra were performed by first reducing samples of CYP121A1 with excess sodium dithionite, followed by bubbling of CO gas and immediately recording spectra between 250 and 700 nm at regular intervals of one scan every 5–10 min for one hour.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is supported by two of our previous studies. First, we utilized protein nuclear magnetic resonance (NMR) to demonstrate that CYP24A1 enzymes from species that are known to display distinctive substrate regioselectivity also rely on different secondary interactions to bind Adx . Subsequently, we also demonstrated that in a carbon-24 hydroxylase system (from rat), allosteric communication exists between the active site and the proximal Adx recognition surface of CYP24A1 …”
mentioning
confidence: 99%